A Confucian Interpretation of Creativity. (4th February 2019) - Tan, Charlene
Abstract: This article explores a Confucian interpretation of creativity with reference to two classics— Analects and Mencius . A Confucian understanding of creativity centers on yi (appropriateness) and is motivated by shu (empathy) for the purpose of broadening dao (Way). Confucian creativity is manifested in two main ways: novelty through original interpretations of the objective world; and appropriateness through flexible responses to concrete circumstances synchronically and diachronically. Two major implications for research on creativity are highlighted. The first is that a Confucian approach to creativity extends the existing research on personal creativity by foregrounding the moral and interpersonal elements. Secondly, Confucian creativity synthesizes novelty and appropriateness, thereby challenging the essentialization of creativity and creative abilities of East Asians. A Confucian conception of creativity transcends a narrow focus on specific creative acts to a broader consideration of the agents, relationships, socio‐cultural contexts and related moral issues.